Macarius of Jerusalem. Letter to the Armenians (AD 335). Introduction, text, translation and commentary by Abraham Terian, Treasures of the Armenian Christian Tradition 4, Crestwood – New York 2008, St. Vladimir’s Seminary Press, ss. 184 - Naumowicz, Józef (Vox Patrum, 2011)
nie dotyczy